2012
DOI: 10.15560/8.2.254
|View full text |Cite
|
Sign up to set email alerts
|

First record for the state of Rondônia and revised distribution map of Chiroderma trinitatum Goodwin, 1958 (Mammalia: Chiroptera: Phyllostomidae) in Brazil

Abstract: In the present work we report the first record of Chiroderma trinitatum Goodwin, 1958 for the state of Rondônia, northern Brazil. A map with all known records of C. trinitatum from Brazil is also presented. The record is based on a fluid preserved specimen with skull removed. The new record, though expected, fills a distributional gap in the Amazonic region of Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
(15 reference statements)
0
5
0
1
Order By: Relevance
“…For the taxonomic determination, we followed taxonomic keys (Gardner 2008, Diaz et al 2016, revisions (Barquez et al 1999, Woodman & Timm 2006, Garbino et al 2012, Ruelas 2017, and the specimens of the MUSM collection for comparisons. The taxonomic nomenclature used by Pacheco et al (2009) was complemented with more recent taxonomic changes (Parlos et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…For the taxonomic determination, we followed taxonomic keys (Gardner 2008, Diaz et al 2016, revisions (Barquez et al 1999, Woodman & Timm 2006, Garbino et al 2012, Ruelas 2017, and the specimens of the MUSM collection for comparisons. The taxonomic nomenclature used by Pacheco et al (2009) was complemented with more recent taxonomic changes (Parlos et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…IDENTIFICATION: Chiroderma trinitatum is distinguished from other congeneric species by its small size (forearm <43 mm, greatest length of skull <23 mm); conspicuous white facial and middorsal stripes; and inner upper incisors that converge only distally, contacting each other at the tips (Gardner, 2008e;Garbino et al, 2012Garbino et al, , 2020Lopez-Baucells et al, 2018). Descriptions and measurements of C. trinitatum were provided by Goodwin (1958), Goodwin and Greenhall (1961), Ojasti and Linares (1971), Baker and Genoways (1976), Gardner (1976), Carter and Dolan (1978), Bergmans (1979), Genoways and Williams (1979), Swanepoel and Genoways (1979), Brosset and Charles-Dominique (1990), Simmons and Voss (1998), Lim et al (2005), Taddei and Lim (2010), Garbino et al (2012), Tello et al (2014), Rocha et al (2016), and Velazco and . No subspecies are currently recognized (Garbino et al, 2020).…”
Section: Genus Artibeus Leach 1821mentioning
confidence: 99%
“…IDENTIFICATION: Chiroderma villosum is easily distinguished from other species in the genus by the following combination of characteristics: medium size (forearm >40 mm, greatest length of skull >23 mm); pale facial and dorsal stripes inconspicuous or absent; and upper inner incisors slender and parallel (not convergent) (Gardner, 2008e;Lopez-Baucells et al, 2018;Garbino et al 2020). Descriptions and measurements of C. villosum were provided by Goodwin and Greenhall (1961), Husson (1962Husson ( , 1978, Hill (1964), Ceballos-Bendezui (1968), Baker and Genoways (1976), Carter and Dolan (1978), Genoways and Williams (1979), Swanepoel and Genoways (1979), Brosset and Charles-Dominique (1990), Simmons and Voss (1998), Lim et al (2005), Taddei and Lim (2010), Garbino et al (2012), and Rocha et al (2016 [who reported Brazilian specimens misidentified as C. salvini]).…”
Section: Genus Artibeus Leach 1821mentioning
confidence: 99%
“…Identification: We consulted descriptions and measurements of Chiroderma trinitatum provided by Goodwin (1958), Goodwin and Greenhall (1961), Baker and Genoways (1976), Gardner (1976), Carter and Dolan (1978), Geno¬ ways and Williams (1979), Swanepoel and Genoways (1979), Brosset and Charles-Dominique (1990), Anderson (1997), Simmons and Voss (1998), Lim et al (2005), Taddei and Lim (2010), Garbino et al (2012), Tello et al (2014), and Rocha et al (2016). Two subspecies are cur¬ rently recognized: C. t. gorgasi (Panama south to western Colombia and northwestern Ecua¬ dor) and C. t. trinitatum (Trinidad, eastern Colombia, Ecuador, and Peru, and Venezuela, the Guianas, Brazil, and northern Bolivia) (Gardner, 2008c).…”
Section: Rhinophylla Pumilio Peters 1865mentioning
confidence: 99%
“…Two subspecies are cur¬ rently recognized: C. t. gorgasi (Panama south to western Colombia and northwestern Ecua¬ dor) and C. t. trinitatum (Trinidad, eastern Colombia, Ecuador, and Peru, and Venezuela, the Guianas, Brazil, and northern Bolivia) (Gardner, 2008c). Our Mayo River basin speci¬ men exhibits the diagnostic characteristics of the nominate subspecies: small size (FA <42.5 mm, GLS <23 mm); dorsal stripe arising between the shoulders and extending across the head; muzzle short and broad; furred legs; uropatagium par¬ tially furred, lack of a conspicuous fringe of hair on its trailing edge; skull lacking nasal bones; and upper inner incisors that converge along their distal third, contacting each other at the tips (Simmons and Voss, 1998;Gardner, 2008c;Garbino et al, 2012). Measurements of our spec¬ imen fall within the range reported for the species.…”
Section: Rhinophylla Pumilio Peters 1865mentioning
confidence: 99%